Vanuatu Health Financing Systems Assessment : Spend Better - World Bank Group (World Bank, Washington, DC, 2018)
This report identifies critical opportunities and constraints faced by the Vanuatu health system as it makes progress toward universal health coverage (UHC). Protecting the achievements that have been made over recent years, while continuing to improve a broader range of health outcomes, requires effective management of changes in financial and other institutional arrangements in the health sector. This health financing systems assessment (HFSA) provides context and emphasizes key issues and messages aimed at providing Ministry of Health (MoH) and partners with a platform to help with this transition. It builds upon other work that has been done in recent years on health in Vanuatu. The assessment begins with an overview of the prevailing economic and fiscal context and key health outcomes. It then overviews the country’s health system - through its human, physical, and financial dimensions. Finally, it reviews health financing in some detail to identify trends across time; against regional benchmarks; and at both national and subnational and facility levels. The assessment concludes with a summary of policy options.